The short-term complications of augmentation cystoplasty: A single center experience (Annals of Medical Research, 2022)
Aim:  To evaluate the short-term complications of various cystoplasty techniques in pediatric population and determine the predicting factors.Materials and Methods: The data of 206 patients (94 males, 112 females) who underwent augmentation cystoplasty between 1991-2016 were analysed retrospectively. Short-term complications within 30 days were evaluated according to the modified Clavien classification system. Grade III, IV, and V were grouped major complications. Chronic renal Disease (CRD) was defined as increasing serum creatinine levels above the normal age-adjusted values. Clinical factors and associated procedures to the surgery (Mitrofanoff procedure, bladder outlet procedures, ureteral anti-reflux surgery) were evaluated to predict overall and major complications.Results: The mean age was 9.8±4.7 years and female/male ratio was 112/94. Overall complication rate was 32% (66 patients) and distributed to Clavien class I, II, IIIb, IVa as 18 (8,7%), 33(16%), 14 (6,81%), 1 (0.48%) patients; respectively. There was no mortality. Age, PUV aetiology and CRD were significant predictor of complication on univariate analysis (p=0.026, p=0.048 and p=0.045, respectively). Age and preoperative CRD were significant on multivariable analysis (p=0.015, OR=0.918 and p=0.046, OR=2.134). Major complications occurred in 15 (7.3%) patients. Bladder exstrophy epispadias complex (BEEC), preoperative CRD, anti-reflux surgery, ileal augmentation were significant parameters on univariate analysis (p=0.007, p=0.003, p=0.043, and p=0.022, respectively). For major complications where BEEC, CRD and ileal AC were significant parameters on multivariate analysis (p=0.009, OR=7.837; p=0.003, OR=9.649, p=0.047, OR=4.241, respectively).Conclusion: Augmentation cystoplasty and associated procedures have acceptable complication rate for pediatric group. Preoperative renal disease and younger age are associated with complications. For major complications, Bladder exstrophy epispadias complex, ileal augmentation and preoperative renal disease are risk factors.